Development of Antibacterial Nanocomposite: Whey Protein-Gelatin-Nanoclay Films with Orange Peel Extract and Tripolyphosphate as Potential Food Packaging. (18th June 2019) - Shams, Behrokh; Ebrahimi, Nadereh Golshan; Khodaiyan, Faramarz
Abstract : Antibacterial and biodegradable whey protein isolate (WPI-) gelatin nanocomposites were prepared using natural orange peel extract (OPE) in percentage of 7, 14, and 21% (v/v solution) and Cloisite 30B (5% w/w dry whey protein) made by a casting method. Mechanical, physical, and antibacterial properties of prepared films were measured as a function of OPE concentration. Higher concentrations of OPE led to higher antibacterial activity, tensile strength, and water solubility, but lower moisture content and transparency. The films microstructures were studied by field emission scanning electron microscopy (FESEM) and ATR-FTIR. Overall, the film containing 21%(v/v) OPE resulted in the best antibacterial, mechanical, and physical performance. Addition of tripolyphosphate (TPP) as a crosslinker to this sample led to the significant increase in transparency. Cloisite 30B, OPE, and TPP can therefore be used to improve the properties of WPI films as a promising natural food packaging.